Assessment a model of financial satisfaction predictors: examining the mediate effect of financial behaviour and financial strain - Falahati, Leila; Sabri, Mohamad Fazli; Paim, Laily (IDOSI Publications, 2012)
Satisfaction with one's financial status can enhance personal satisfaction and more broadly, life satisfaction and in contrast financial difficulties and dissatisfaction with one's financial status can lead to stress and depression. Research related to financial satisfaction revealed financial behaviour has a major contribution to satisfaction or dissatisfaction with financial situation. More importantly it is documented that financial behaviour is affected by other factors such as the level of financial literacy, financial attitude, childhood consumer experiences, influence of primary and secondary socialization agents as well. The purpose of this study is to assess factors predict financial satisfaction and furthermore examining the mediate effect of financial behaviour on the relationship between financial literacy, financial attitude, childhood consumer experiences, influence of primary and secondary socialization agents and financial satisfaction. A sample of 700 university students from 11 universities (six Public and five private) were selected using stratified sampling method. Data was collected by self-administered questionnaire. The research estimated model was tested using Structural Equation Modelling (SEM) through AMOS and the mediation approach of Baron and Kenny (1986) using Amos was applied to assess the mediating effect of financial behaviour and financial strain. Results indicated that financial attitude, childhood consumer socialization, socialization agents, financial literacy, financial behaviour and financial strain contribute to predict financial satisfaction. Furthermore the mediation effect of financial behaviour was examined.